Alloying Driven Multifold Fermion‐to‐Weyl Semimetal Transition in CoSi1−xAx (A = Ge, Sn). Issue 8 (19th June 2022) - Dai, TianAo; Li, Yizhi; Zhao, Lingling; Zhao, Xiangmiao; Zhong, Jianxin; Meng, Lijun
Abstract : Multifold chiral fermions with high‐fold degeneracy beyond the twofold Weyl fermions have recently been reported in the transition metal silicide CoSi (space group P 21 3). Here, by alloying parent compound CoSi, an alloy engineering approach to realize different topological phases in CoSi1− x A x (A = Ge, Sn) is demonstrated. By using first‐principles calculations and symmetry analysis, it is shown that the gradual decrease of crystal symmetry due to alloying makes Weyl‐type low‐energy excitation phases appear in CoSi1− x A x . For the alloy structures considered, surface states (SS) and Fermi arcs (FAs) are investigated, and the dynamic stability of the alloy structures is also confirmed by the phonon spectrum. These findings provide a feasible method for customizing the fermion behavior of multifold fermions semimetal and expect future experimental verification. Abstract : This article demonstrates an alloy engineering approach to realize different topological phases in CoSi1− x A x (A = Ge, Sn). By using symmetry analysis, it is shown that the gradual decrease of crystal symmetry due to alloying makes Weyl‐type low‐energy excitation phases appear in CoSi1− x A x . These findings provide a feasible method for customizing the fermion behavior of multifold fermions semimetal.